2019
DOI: 10.4236/jbise.2019.122012
|View full text |Cite
|
Sign up to set email alerts
|

Applying Deep Learning Models to Mouse Behavior Recognition

Abstract: In many animal-related studies, a high-performance animal behavior recognition system can help researchers reduce or get rid of the limitation of human assessments and make the experiments easier to reproduce. Recently, although deep learning models are holding state-of-the-art performances in human action recognition tasks, these models are not well-studied in applying to animal behavior recognition tasks. One reason is the lack of extensive datasets which are required to train these deep models for good perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…In most cases the ground truth is not perfectly defined and contains a lot of variability. Additionally, there is currently a lack of extensive, well-annotated data-sets, and many studies use older labeled data from previous studies [52][53][54]. A potential approach could be to create extensive, well-annotated labeling sets, which include only examples where all raters agree with one another, however these would omit difficult cases from the training set and thus limit the sensitivity of the classifier.…”
Section: Big Data Big Problems Small Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases the ground truth is not perfectly defined and contains a lot of variability. Additionally, there is currently a lack of extensive, well-annotated data-sets, and many studies use older labeled data from previous studies [52][53][54]. A potential approach could be to create extensive, well-annotated labeling sets, which include only examples where all raters agree with one another, however these would omit difficult cases from the training set and thus limit the sensitivity of the classifier.…”
Section: Big Data Big Problems Small Solutionsmentioning
confidence: 99%
“…However, this was only the case when heavy data augmentation was applied and the performance dropped a lot when videos from different set-ups/animals were used. A third study [ 54 ] showed a slight increase when using 3D-CNN models pre-trained to recognize human behaviors and retrained with mouse homecage behavior data from a previous study [ 27 ]. However, in this study only 12 similar side-view recordings from the same set-up are used, so it cannot be assessed how well it would perform with a different set-up.…”
Section: From Human Annotation To Machine Learningmentioning
confidence: 99%
“…Behavior modelling and activity interpretation are of increasing interest in the information society [5]. The research on behavior cognition mainly focuses on computer science and network and social psychology, and the research targets mainly include human [6], animal [7], traffic [8], [9] and robot [10]. The Google team proposed in 2006 that the motion behavior cognition system should be composed of four modules of ''sensor-identification-transformation-controlled system (SITR)'' [11].…”
Section: A Behavior Cognitionmentioning
confidence: 99%
“…When an emergency situation arises, decision-making can be based on the gathered data which can be sometimes incomplete or irrelevant. An emergency response system created for the police station helps them to identify the terrorist outbreaks and criminal offenses in advance (Nguyen et al, 2019). By means of combining the different…”
Section: Emergency Response Systemmentioning
confidence: 99%